Pemberdayaan Ibu Rumah Tangga Melalui Pelatihan Kuliner Ikan Di Desa Keranji Guguh Kabupaten Siak - Neng Susi; Syafrani Syafrani; Vonny Indah Sari (Asosiasi Dosen Akuntansi Indonesia, 2022)
The largest area of Keranji Guguh Village is designated for plantation land, as many as 463 plots with an area of 805.42 H of the 884 land parcels in Keranji Guguh Village with an area of 1,337.20 Ha (including rivers/lakes, roads, ditches). When viewed from the livelihoods of the people of Kampung Keranji Guguh, his profession is as a farmer or farm laborer. In development, human factors have a very important position and role, namely humans are development subjects who act as development actors to enjoy the development carried out. The ultimate goal is to increase the welfare of the community. According to the village head, in the near future, the lake in the village will be used as eco-tourism because the lake is on the side of the highway and there are many fish ponds in the lake. One of the ecotourism commodities that will be promoted is culinary made from fish in addition to other culinary delights. Currently, the PKK group of women from Keranji Guguh Village are facing the problem that they have not done processing made from fish because their knowledge and technology are still limited, which is caused by a lack of information about fish processing. After the training, there was an increase in knowledge of fish processing.